FORMULATION AND OPTIMIZATION AND IN VITRO CHARACTERIZATION OF OLANZAPINE LIPOSOME - VANI, G. NETHRA; ALAGUSUNDARAM, M.; CHANDRASEKAR, K. B. (International Journal of Applied Pharmaceutics, 2021)
Objective: Olanzapine (OZ) is a thioeno benzodiazepine class second-generation or atypical antipsychotic that selectively binds to central dopamine D2 and serotonin (5-HT2c) receptors used for the treatment of schizophrenia and bipolar disorder. The present paper is aimed at developing an optimized liposome-loaded OZ as an approach for brain targeting through the nasal route for effective therapeutic management of schizophrenia. Methods: The OZ liposomes were prepared by the thin-film hydration method. Various independent variable such as phospholipid, cholesterol and sonication time was optimized by using Design-Expert® Software to obtain the dependent variables of entrapment efficiency, vesicle size and zeta potential. The optimized formulation was predicted based on the response obtained by the point prediction method. Results: The entrapment efficiency of the formulation was range between 72.9 and 85.1 %. The average particle size of all the 15 experimental runs lies between the minimum and maximum values of the size 258.33 to 325.32 nm, respectively. The zeta potential ranges from-27.53 to-11.46 mV. The optimized formulation for characterized for its morphology by Transmission Electron Microscopy (TEM). In vitro release studies of OZ-loaded liposomal formulation was carried by dialysis sac method using pH 7.4 phosphate buffer (PBS) as a medium. The maximum release was found to be 98.43±1.2 % up to 24 h. The R2 zero-order kinetics and Korsmeyer-Peppas model was found to be 0.9919 and 0.9664, respectively. The zero-order shows the best-fit model with a highest R2 value exhibiting better correlation and the ‘n’ value was also found to be 0.85; indicating both diffusion-controlled and swelling-controlled drug release that is anomalous transport. Conclusion: The results, clearly states that the prepared formulations justify the parameters and OZ might be a suitable candidate to target the brain through nasal delivery.